Medical scientific conferences and social networks: How Russian physicians share professional knowledge? - Аlexandr Е. Alfimov; Аnzhelika А. Trofimova; Аrseniy А. Matvienko; Мarina V. Kodalaeva (Digital Diagnostics, 2023)
BACKGROUND: Physicians who attend international conferences cover their content on social media. Such posts generate an active response and discussion in the comments involving other physicians. Attending all conferences when they are held simultaneously is impossible; therefore, brief communications that capture the essence of a missed presentation are in demand, generate an immediate response, and quickly raise awareness of new clinical research and scientific data. This phenomenon was not studied in Russia. However, the posts were analyzed and the activity and interest among Russian physicians were evident.